2019
DOI: 10.1186/s12931-019-0976-3
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal high fat diet compromises survival and modulates lung development of offspring, and impairs lung function of dams (female mice)

Abstract: BackgroundEpidemiological studies have identified strong relationships between maternal obesity and offspring respiratory dysfunction; however, the causal direction is not known. We tested whether maternal obesity alters respiratory function of offspring in early life.MethodsFemale C57Bl/6 J mice were fed a high or low fat diet prior to and during two rounds of mating and resulting pregnancies with offspring lung function assessed at 2 weeks of age. The lung function of dams was measured at 33 weeks of age.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…In our study, reduced litter sizes and offspring survival rates were observed in obese mice. These results are consistent with a recent study that reported decreased litter survival in mice fed a high-fat diet (Smoothy et al, 2019). Our previous study found that PC gavage improved litter sizes and survival rates in D-galinduced aging mice (Li et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, reduced litter sizes and offspring survival rates were observed in obese mice. These results are consistent with a recent study that reported decreased litter survival in mice fed a high-fat diet (Smoothy et al, 2019). Our previous study found that PC gavage improved litter sizes and survival rates in D-galinduced aging mice (Li et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, HFHS feeding increased litter size regardless of physical activity levels. The data on the influence of maternal HFD and/or exercise on litter size are, however, inconsistent [10,[30][31][32]. Since in favourable conditions an increase in litter size may be favoured [33], it could be speculated that HFHS animals allocated more energy to increase litter and offspring size.…”
Section: Animal Characteristics and Model Of Gdmmentioning
confidence: 99%
“…There is less evidence of interactions between dietary lipids, the microbiome and lung mucus barrier in healthy states. Although mice fed HFDs have altered GI microbiome composition and develop respiratory inflammation, histopathology and impaired lung function, they do not have altered lung mucus production without another stimulus such as in disease models 57,90,133 . More detailed analysis of mucus composition and characterization of the respiratory microbiome would provide further insights.…”
Section: Macronutrients: Impact On Microbiome and Mucous Barriermentioning
confidence: 99%